1986
DOI: 10.1210/jcem-63-5-1065
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Characteristics of the Gonadotropin-Releasing Hormone Analog D-Ser(TBU)-6EA-10Luteinizing Hormone-Releasing Hormone (Buserelin) after Subcutaneous and Intranasal Administration in Children with Central Precocious Puberty

Abstract: A double antibody RIA was developed for the measurement of the long-acting GnRH agonist D-Ser(TBU)6EA10GnRH (buserelin). The antibody, raised in rabbits against a buserelin-hemocyanin conjugate, reacted with the intact molecule and also molecular fragments containing the C6-9 tetrapeptide sequence and permitted the measurement of buserelin activity in serum and urine. Natural GnRH, LH, and FSH did not cross-react in this assay system. The assay was applied to samples obtained from children receiving buserelin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 13 publications
2
11
1
Order By: Relevance
“…These clinical observations emphasize the role of the dosage of the agonist using the intranasal route, in agreement with the experimental doseresponse studies in rats and dogs [19,34] and in adult man [37]. The poor intranasal absorption (less than 5%) of GnRH [5] and its agonist, Buserelin [20,30] probably accounts for the particular importance of the dosage using the intranasal route. Although serum Buserelin concentrations achieved after intranasal administration are several times lower than after subcutaneous injection of a similar dose [20,30], we found that a daily intranasal dose of 1200 gg Buserelin, not associated with cyproterone, could be effective in initiating the inhibition of pituitary-gonadal function.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…These clinical observations emphasize the role of the dosage of the agonist using the intranasal route, in agreement with the experimental doseresponse studies in rats and dogs [19,34] and in adult man [37]. The poor intranasal absorption (less than 5%) of GnRH [5] and its agonist, Buserelin [20,30] probably accounts for the particular importance of the dosage using the intranasal route. Although serum Buserelin concentrations achieved after intranasal administration are several times lower than after subcutaneous injection of a similar dose [20,30], we found that a daily intranasal dose of 1200 gg Buserelin, not associated with cyproterone, could be effective in initiating the inhibition of pituitary-gonadal function.…”
Section: Discussionsupporting
confidence: 72%
“…The poor intranasal absorption (less than 5%) of GnRH [5] and its agonist, Buserelin [20,30] probably accounts for the particular importance of the dosage using the intranasal route. Although serum Buserelin concentrations achieved after intranasal administration are several times lower than after subcutaneous injection of a similar dose [20,30], we found that a daily intranasal dose of 1200 gg Buserelin, not associated with cyproterone, could be effective in initiating the inhibition of pituitary-gonadal function. During long-term administration of GnRH agonists, gonadotropin responses to a single injection of GnRH [4,26,28,32,38,39] or to pulsatile administration of GnRH [14] as well as spontaneous pulsatile LH secretion [28,38,39] are abolished.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody development does not appear to be obligatory after GnRH treatment, but it does appear to occur more frequently in patients who develop complications in relation to the treatment [48,49]. Although no specific pathophysiological mechanisms have been confirmed, polymorphisms of the LH receptor gene and concomitant endometriosis have been suggested as triggering factors for developing gastrointestinal dysmotility in response to GnRH analogs [46].…”
Section: Gastrointestinal Dysmotility and Antibody Formation After Gnmentioning
confidence: 99%
“…In some publications with relatively large numbers of treated patients, FH is only reported for those children in which FH was attained at the time of publication. The figures are often promising but the bias towards less serious cases must be suspected as those with a very early CPP were probably not yet at their FH [32,63,64].…”
Section: Comparisons Between Agonist Treatment and No Treatmentmentioning
confidence: 99%